Linguistic functions of emoji in social media communication - Muhammad Hasyim, Burhanuddin Arafah, (Opción, 2019)
This paper aims to discuss the emoji linguistic function in conversations on WhatApps social media. This paper uses Barthes and Morris’s semiotic approach. Data collection methods are the distribution of questionnaires online, and photo documentation (screenshot) of conversations using emojis on WA social media. The results of the study concluded that emojis are part of the grammatical elements of language in communicating on social media. In conclusion, semiotic, emoji is a sign vehicle, designatum, and interpretant relation that produces syntactic, semantic and paradigmatic emoji dimensions of signs as a linguistic function in social media communication.